2021
DOI: 10.48550/arxiv.2110.06240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Residual Abundances in GALAH DR3: Implications for Nucleosynthesis and Identification of Unique Stellar Populations

Emily J. Griffith,
David H. Weinberg,
Sven Buder
et al.

Abstract: We investigate the [X/Mg] abundances of 16 elements for 82,910 Galactic disk stars from GALAH+ DR3. We fit the median trends of low-Ia and high-Ia populations with a two-process model, which describes stellar abundances in terms of a prompt core-collapse and delayed Type-Ia supernova component. For each sample star, we fit the amplitudes of these two components and compute the residual ∆[X/H] abundances from this two-parameter fit. We find RMS residuals 0.07 dex for well-measured elements and correlated residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Section 4 maps the age-abundance relations for [Ba/Fe] and [Eu/Fe], across the [𝛼/Fe]-[Fe/H] plane. The overall mean relations between age-[Ba/Fe] and age-[Eu/Fe] reported in this study broadly match that from previous work focusing both on stellar populations in the field (e.g., da Silva et al 2012;Reddy & Lambert 2015;Nissen 2016;Nissen et al 2017;Bedell et al 2018;Hayden et al 2020;Griffith et al 2021a) and in open/globular clusters (e.g., D 'Orazi et al 2009;Maiorca et al 2011;Magrini et al 2018). These suggest that younger stellar populations manifest on average higher contributions from the 𝑠-process nucleosynthetic channel (although possibly not in the same amounts for different 𝑠-process elements, see D 'Orazi et al 2017 andLambert 2017).…”
Section: Age-abundance Profiles Of Neutron Capture Elements In the Ga...supporting
confidence: 88%
“…Section 4 maps the age-abundance relations for [Ba/Fe] and [Eu/Fe], across the [𝛼/Fe]-[Fe/H] plane. The overall mean relations between age-[Ba/Fe] and age-[Eu/Fe] reported in this study broadly match that from previous work focusing both on stellar populations in the field (e.g., da Silva et al 2012;Reddy & Lambert 2015;Nissen 2016;Nissen et al 2017;Bedell et al 2018;Hayden et al 2020;Griffith et al 2021a) and in open/globular clusters (e.g., D 'Orazi et al 2009;Maiorca et al 2011;Magrini et al 2018). These suggest that younger stellar populations manifest on average higher contributions from the 𝑠-process nucleosynthetic channel (although possibly not in the same amounts for different 𝑠-process elements, see D 'Orazi et al 2017 andLambert 2017).…”
Section: Age-abundance Profiles Of Neutron Capture Elements In the Ga...supporting
confidence: 88%
“…This work also extends upon the work of Weinberg et al (2019) and Griffith et al (2021a), who showed that abundance trends throughout the bulge and disk are independent of galactic location for the α-sequences, and that a star's abundance pattern can be represented as a sum of contributions from SNIa and SNII. Griffith et al (2021b) and Weinberg et al (2021) extend the two-process model used in their previous work to galah+ DR3 and apogee DR17 elements, and find that the correlations of the residuals reveal underlying structure such as common nucleosynthetic enrichment sources. In these recent works, the analyses were done on two groups by modeling the data for the α-sequences separately.…”
Section: Introductionmentioning
confidence: 72%
“…The level of chemical homogeneity for fixed [Fe/H], [Mg/Fe], and age in the current day disk that we find is in agreement with previous work. With a two-process model that uses the weighted sum of SNII and SNIa, Weinberg et al (2021), Griffith et al (2021a), andGriffith et al (2021b) showed that residuals for most abundances in the Milky Way disk are similar for the 16 elements they studied (≤ 0.07 dex), with the residual in Ce being significantly larger (∼ 0.1 dex). Ness et al (2022) goes further to argue that the disk is homogeneous in supernovae elements to 0.01 -0.015 dex at fixed birth radius and time.…”
Section: Discussionmentioning
confidence: 91%